河川結氷時の塩水遡上に関する基礎的研究 - 吉川, 泰弘; 赤堀, 良介; 安田, 浩保; 平井, 康幸 (Journal of Japan Society of Civil Engineers, Ser. B1 (Hydraulic Engineering), 2012)
This study aimed to clarify the fundamental phenomenon of salinity intrusion in ice covered river. We carried out salinity intrusion experiment to which model ice-sheet floats on the water surface and one-dimensional two-layered unsteady flow calculation. In this experiment, the vertical flow velocity was measured using particle image velosimetry technique. In the experiment in which ice-sheet exists, the model ice-sheet indirectly attenuated the salinity intrusion because Reynolds number does not become large. Shear stress was computed by having assigned the experiment data to one-dimensional two-layered unsteady flow equation. In both ice and no-ice condition, Interface shear stress has large influence on salinity intrusion. It was shown that the calculation model built by this study can reproduce salinity intrusion experiment. journal article